Models for Multiparty Engagement in Open-World Dialog - Bohus, Dan; Horvitz, Eric (Proceedings of the SIGDIAL 2009 Conference, The 10th Annual Meeting of the Special Interest Group on Discourse and Dialogue, 2009)
We present computational models that allow spoken dialog systems to handle multi-participant engagement in open, dynamic environments, where multiple people may enter and leave conversations, and interact with the sys-tem and with others in a natural manner. The models for managing the engagement process include components for (1) sensing the engagement state, actions and intentions of multiple agents in the scene, (2) making engagement decisions (i.e. whom to engage with, and when) and (3) rendering these decisions in a set of coordinated low-level behaviors in an embodied conversational agent. We review results from a study of interactions "in the wild" with a system that implements such a model.